The Response of Insects and Weeds within the Crop to Variation in Sowing Density of Canola - Lucie Vykydalová; Petra Martínez Barroso; Igor Děkanovský; Eva Hrudová; Yentriani Rumeta Lumbantobing; Markéta Michutová; Jan Winkler (Land)
The relationships between weeds and insects in canola stands with different seeding rates are not fully understood. Varying seeding rates in canola crops can create different conditions that affect both weed and insect populations and their interactions. The aim of this work was to determine the response of weeds and insects of selected taxa to different densities of canola stand densities and to clarify the interactions between weeds and insects in canola stands. The field experiment was conducted on a plot located in the cadastral area of the municipality of Pěnčín (Moravia, Czech Republic). The results show that a reduced canola sowing rate of oilseed rape leads to increased weed infestation, which is dominated by one taxon (Papaver rhoeas L.). The increase in weed infestation of canola stands is not reflected in an increase in the diversity of captured insects. Increased canola seeding rate improves weed suppression but increases the number of canola pest insects. A higher number of plants and more canola biomass increase the food supply and, thus, make the stand more attractive to canola pests. The taxon Brassicogethes aeneus dominated the pests species spectrum. Changing the seeding rate of canola results in a response in weed and insect populations. The standard recommended seeding rate is optimal in terms of competitive suppression of weeds and the occurrence of pests and trapped insects. Increasing or decreasing the seeding rate of rapeseed does not bring any benefits in terms of pest regulation or biodiversity. However, the results obtained indicate an interesting weed–insect interaction in the conditions of canola stands.